2016
DOI: 10.1063/1.4960606
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced Ag2Te polymorphs in conjunction with topological non trivial to metal transition

Abstract: Silver telluride (Ag2Te) is well known as superionic conductor and topological insulator with polymorphs. Pressure induced three phase transitions in Ag2Te have been reported in previous. Here, we experimentally identified high pressure phase above 13 GPa of Ag2Te by using high pressure synchrotron x ray diffraction method in combination with evolutionary crystal structure prediction, showing it crystallizes into a monoclinic structure of space group C2/m with lattice parameters a = 6.081Å, b = 5.744Å, c = 6.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This is followed by structural transitions to metallic phases III and IV. The recent measurements of transport properties under pressure by Zhang et al 11 and Zhu et al 12 showed a collapse of the resistivity at the isostructural transition, while the temperature dependence confirmed a semiconducting behavior up to 11 or slightly beyond 12 the isostructural transition and fully metallic beyond it. At low pressures the MR has a quadratic dependence on temperature followed by linear dependence without saturation, changing to purely quadratic as the pressure is increased.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…This is followed by structural transitions to metallic phases III and IV. The recent measurements of transport properties under pressure by Zhang et al 11 and Zhu et al 12 showed a collapse of the resistivity at the isostructural transition, while the temperature dependence confirmed a semiconducting behavior up to 11 or slightly beyond 12 the isostructural transition and fully metallic beyond it. At low pressures the MR has a quadratic dependence on temperature followed by linear dependence without saturation, changing to purely quadratic as the pressure is increased.…”
Section: Introductionmentioning
confidence: 90%
“…Since the P21/c structure is maintained through this transition, it must correspond to the electronic isostructural transition identified in previous work. 11,12 The unit cell volume plotted in Fig. 1(c) shows discontinuities at the two structural phase transitions and the inset one at between 1.9 and 2.3 GPa due to the isostructural transition as in Ag2Te.…”
Section: A Structurementioning
confidence: 98%
See 3 more Smart Citations